(3ecQ GdbQOIs ((3GdbGgQIs (3hKjbIs, 2006)
(3GdMjhGfGJ JYjT aj GdZGHI hJNGa GdCSO, dCfg Cbhj GdMjhGfGJ aj GdZGHI ,PGJ eQI ZVH GdbQO ef GdCSO hef HbjI GdMjhGfGJ aacQ aj MjdI jJNdU HgG efge (B.(3LeY GdbQO GdcHjQ HbjI GdbQhO hWdH efge Cf jMaQhG MaQI cHjQI djMaXhG ajgG GdeGA aeGPG MOK?s
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdbQOs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs